Potential carbon emission reductions in australian construction systems through bioclimatic principles. (May 2016) - Sattary, Sattar; Thorpe, David
Abstract: The building sector responsible for 40 per cent of energy use (UNEP SBCI Sustainable Buildings and Climate Initiative, 2010 ); by 2030, a total of 60 Mt of carbon-reduction opportunities can be found in the Australian building sector (McKinsey, 2008 ). Reduction in the carbon emissions from Australian buildings is thus a priority for the Federal government. In Australia the government recently announced plan to cut emissions by 26–28 per cent by 2030 (Federal Politics, 2015 ). This study concerns energy use in building construction and the degree of carbon emissions reduction that can be achieved through use of bioclimatic principles. Criteria of the model proposed in this research have been developed through analyzing bioclimatic principles to measure the potential construction carbon emissions that can be reduced in pre-construction and construction (cradle to site) stages during the lifecycle stages of a building. The developed model examines six case studies from Australia and the UK. The outcomes of this research clearly shows that by use of bioclimatic principles up to 65 per cent reduction in construction carbon emissions can be achieved for a whole building systems (floor, wall and roof), while current best construction practice (i.e. a graded by Green Star) at the highest level achieve less than 32 per cent reduction. However the future of the green construction industry lies on taking into account the bioclimatic principles- such as replacing conventional building materials with more energy efficient materials (i.e. replacing Portland cement with geopolymer based cement); reusing the recycled construction materials; reducing transportation and other similar initiatives.